2008
DOI: 10.1007/s11294-008-9178-3
|View full text |Cite
|
Sign up to set email alerts
|

International Implications of the Cost of Compliance with the External Audit Requirements of Section 404 of Sarbanes–Oxley

Abstract: Audit fees, Compliance cost, Cross listing, International implications, Sarbanes–Oxley, M41,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…Ghosh and Pawlewicz (2007) documented an increase in audit fees by approximately 77 percent for the years following the introduction of SOX. Bhamomsiri et al (2009) maintained similar results, indicating that audit fees increased by an average of 65 percent for the initial group of filers in the first year SOX 404 became effective. Similarly, Swartz (2008) reported significant audit fee increases for small firms, and Cosgrove and Niederjohn (2008) provided evidence of higher audit fees across all firms.…”
Section: Audit Fees and Regulationmentioning
confidence: 58%
“…Ghosh and Pawlewicz (2007) documented an increase in audit fees by approximately 77 percent for the years following the introduction of SOX. Bhamomsiri et al (2009) maintained similar results, indicating that audit fees increased by an average of 65 percent for the initial group of filers in the first year SOX 404 became effective. Similarly, Swartz (2008) reported significant audit fee increases for small firms, and Cosgrove and Niederjohn (2008) provided evidence of higher audit fees across all firms.…”
Section: Audit Fees and Regulationmentioning
confidence: 58%
“…In this regard, Bedard et al (2008) found evidence of a reduction in risk adjustment of audit fees for accelerated companies resulting from the extensive internal control testing under SOX 404. Related research has found that smaller firms have higher audit risk (Bhamornsiri, Guinn & Schroeder, 2009). 2 H6: Regulated companies exhibited stronger positive linear trends in the period 2006-2009 for both accelerated and non-accelerated companies.…”
Section: Hypothesesmentioning
confidence: 99%
“…They also imply that audit fees for smaller companies will continue to increase whether or not they come under the SOX 404 provisions. Bhamornsiri et al (2009) suggest that smaller firms have relatively weaker internal control structures that require additional audit analysis and predict that smaller companies will experience further increases in audit fees when they become fully subject to the provisions of SOX. Charles et al (2010) found a significant positive association between audit fees and financial reporting risk during the period 2000-2003.…”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations